Comparative efficacy of bromocriptine, cabergoline and thyroxine in inducine oestrus in bitches - Ajitkumar G (Department of Animal Reproduction, Gynaecology and Obstetrics, College of Veterinary and Animal Sciences, 2008)
Detailed survey on breeding, feeding and management of 1721 dogs belonging to 817 owners was conducted in different parts of Kerala State. Among the dogs surveyed, 518 (30.10%) were male and 1203 (69.90%) were female. Breed-wise details of dogs maintained by individual owners revealed German shepherd dog (20.74%) as the most popular breed of dog followed by Labrador retriever (18.13%), Dachshund (11.39%), Rottweiler (9.12%) and Spitz (5.52%). The percentage of local non-descript dogs was found to be 14.64 only. The prevalence, nature and magnitude of anoestrus among the female dogs were evaluated based on breeding details. Haematological, hormonal, mineral and cholesterol profile of anoestrous bitches were estimated.